Climate change and changes in the baseline of coastline countries: solutions and challenges - Homayoun Habibi; Hajar Raee Dehaghi (علوم محیطی)
Introduction: Human ability to transform the environment raised a new environmental concern all over the globe, namely climate change. Today, global warming and sea level rise resulted from polar ice melting are the most immediate, definitive, and visible effects of climate change. One of the effects of these changes is the likelihood that coastal states, especially small island states, will be deprived of their former maritime zones. Since the baseline is the basis of determination of the maritime zones of the coastal state, with sea level rise, the validity of previous baselines and countries' eligibility for making use of maritime zones have been challenged. It raises the question of whether such countries are still eligible to use the existing baselines or should redraw baselines based on changes. The purpose of this paper was to examine the effects of climate change on baselines of the coastal and archipelagic states and to provide solutions to these countries to counter such effects. Material and methods: In order to examine the impacts of climate change on coastal countries, we first discussed the effects of climate change on the oceans. Research shows that the most important of these changes is global warming and sea level rise. Then, the impact of such consequences on the normal and direct baselines of the coastal and archipelagic states was analyzed. Results and discussion: We concluded that the most important effects of such changes on the oceans are global warming and sea level rise. Then, the impact of climate change on the baselines and the authenticity of this legal challenge were assessed. It was concluded that however the Convention on the Law of the Sea 1982 neglected the potential of future changes to base points, by interpreting the drawing of baselines of unstable coastlines and continental shelf, it is possible to accept the right of coastal and archipelagic states to preserve the existing baselines and maritime zones despite sea level changes. Conclusion: This study concluded that the consequences of climate change undoubtedly lead to widespread changes in baselines, and by interpreting the provisions of the convention, it can provide solutions to counter these changes, and eventually, acknowledge the right of coastal states to preserve their former baselines.